IMMUNOCHEMICAL STUDIES ON BLOOD GROUPS : VII. CHEMICAL CHANGES ASSOCIATED WITH DESTRUCTION OF BLOOD GROUP ACTIVITY AND ENHANCEMENT OF THE TYPE XIV CROSS-REACTIVITY BY PARTIAL HYDROLYSIS OF HOG AND HUMAN BLOOD GROUP A, B, AND O SUBSTANCES - Kabat, Elvin A. (The Rockefeller University Press, 1948)
1. The effect of heating at varying pH on the cross-reactivity of hog blood group A and 0 substances with Type XIV antibody has been investigated. The hydrolysis of blood group A, B, and O substances from hog and human sources at pH 1.5–1.8 resulted in destruction of blood group activity and a marked increase in cross-reactivity with Type XIV antipneumococcus horse serum. 2. Analysis revealed the liberation of reducing sugar, most of which was dialyzable. It was further shown that the major part of the reducing sugar was fucose with small amounts of free and polymerized galactose and glucosamine. Non-glucosamine nitrogen, probably amino acids, also was found in the dialysate. 3. Paper chromatographic separation of the concentrated dialysate confirmed the presence of fucose and showed that the majority of the galactose and glucosamine occurred in polymeric form. 4. Quantitative analysis of the substances isolated from the paper showed good recovery of the various components, indicating that practically all of the material in the dialysate could be accounted for. 5. The methylpentose of human blood group A substance was identified as fucose. 6. The structure of the blood group substances is interpreted in terms of these results.